(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article delves into the historical evolution of railway stations, tracing their emergence from ancient times to their modern-day significance in shaping transport networks. It explores the developmental stages of road infrastructure networks, highlighting the pivotal role of railway stations in facilitating connectivity and mobility. The article addresses the challenges encountered in the establishment and operation of railway stations, both historically and in contemporary times. By examining past and present issues, this article offers insights into the complexities of transport networks and the strategies needed to overcome emerging challenges